DEVELOPMENT OF NANOMATERIALS TO INCREASE THE PERFORMANCE OF SILICON ELECTRONICS - Asanov, D.J.; Ashirbekova, S.U. (SCIENCE and SOCIETY, 2024)
The development of highly efficient and fast semiconductor components, as well as ultra-large integrated circuits (VLSI), requires the use of new materials in production processes. One of the most promising materials for modern microelectronics are metal silicides. These connections are widely used in solid-state electronics, in particular, to create rectifier and ohmic contacts, as well as conductive elements in integrated circuits. In addition, magnesium silicide single crystals exhibit excellent thermal efficiency characteristics, which makes magnesium and silicon attractive materials for creating thin-film semiconductor compounds such as MgSi, which have high thermal efficiency.